MULTILEVEL ANALYSIS OF DETERMINANT OF DEATH OF INDONESIAN HAJJ PILGRIMS 2022-2024: DETERMINANT OF DEATH OF INDONESIAN HAJJ PILGRIMS - Pramita, Wiwid; Djafri, Defriman; Putri , Ade Suzana Eka (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2025)
Background: The Hajj pilgrimage is an annual religious activity carried out at specific times, locations, and activities, attended by millions of Muslims from around the world (mass gathering). Indonesia, as the country with the largest number of Hajj pilgrims, faces serious challenges in terms of relatively high pilgrim mortality rates each year. Data indicates that the mortality rate of Indonesian Hajj pilgrims peaking at 3.38‰ in 2023. Pilgrim deaths are influenced by various factors, including individual factors, factors related to the the Hajj, and environmental factors. This study aims to identify the factors influencing mortality among Indonesian hajj pilgrims during the Hajj pilgrimage period from 2022 to 2024. Methods: This cross-sectional study consisted of 1,686 samples from the Hajj Health Center data source, Indonesian Ministry of Health (SISKOHATKES SHAR'I) and environmental data from NASA POWER. Results: The determinants of death with p<0.05 were age, gender, history of anemia, history of hypertension, high-risk health status, and history of chronic respiratory disease. The individual level was the most significant contributor to the outcome, accounting for 75,29%. Conclusion: Knowing the determinants of pilgrim mortality enables health education to be implemented from the first health examination and can also be carried out in collaboration with the Hajj Organizing Agency through the existing KBIH.